2016
DOI: 10.1371/journal.pone.0161208
|View full text |Cite
|
Sign up to set email alerts
|

Former Abusers of Anabolic Androgenic Steroids Exhibit Decreased Testosterone Levels and Hypogonadal Symptoms Years after Cessation: A Case-Control Study

Abstract: AimsAbuse of anabolic androgenic steroids (AAS) is highly prevalent among male recreational athletes. The objective of this study was to investigate the impact of AAS abuse on reproductive hormone levels and symptoms suggestive of hypogonadism in current and former AAS abusers.MethodsThis study had a cross-sectional case-control design and involved 37 current AAS abusers, 33 former AAS abusers (mean (95%CI) elapsed duration since AAS cessation: 2.5 (1.7; 3.7) years) and 30 healthy control participants. All par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
115
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 38 publications
(40 reference statements)
6
115
1
3
Order By: Relevance
“…Indeed, it has been reported that oral administration of androgens decreases both T (a well-known withdrawal phenomenon experienced when the athletes are approaching competitions and associated urinary anti-doping tests) and SHBG concentrations 23 24. Recently, Rasmussen et al showed that a significant proportion of former androgen abusers exhibit moderately or notably lowered testosterone levels years after cessation of androgen abuse 25. However, our male throwers did not show decreased LH concentrations (a reported consequence of doping with androgens via the negative feedback loop of the hypothalamic-pituitary-gonadal axis) 26.…”
Section: Discussioncontrasting
confidence: 50%
“…Indeed, it has been reported that oral administration of androgens decreases both T (a well-known withdrawal phenomenon experienced when the athletes are approaching competitions and associated urinary anti-doping tests) and SHBG concentrations 23 24. Recently, Rasmussen et al showed that a significant proportion of former androgen abusers exhibit moderately or notably lowered testosterone levels years after cessation of androgen abuse 25. However, our male throwers did not show decreased LH concentrations (a reported consequence of doping with androgens via the negative feedback loop of the hypothalamic-pituitary-gonadal axis) 26.…”
Section: Discussioncontrasting
confidence: 50%
“…A total of 100 participants were included (current AAS abusers, n=37; former AAS abusers, n=33 and control participants, n=30). Demographics, details on training, extent of AAS abuse, plasma testosterone and SHBG concentrations among the participants have been described elsewhere . Total and free testosterone in plasma differed among all three groups, being clearly higher among current abusers and lower among former AAS abusers compared with control participants (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, official pharmacological data of testosterone derivates concern patients as opposed to athletes, clinical dosages are a fraction of dosages used by athletes, and athletes use mostly unofficial delivery and production lines of AAS. There is, however, reasonable evidence indicating that AAS use is associated with injuries such as tendon ruptures, cardiovascular toxicity, psychopathology such as mood and anxiety disorders, and hypogonadism after cessation of use—so‐called post‐AAS‐hypogonadism …”
Section: Introductionmentioning
confidence: 99%